Exploring Student Satisfaction In Technology-Enhanced Learning And Institutional Competitiveness: A Systematic Literature Review - Salya R. Susanto; Herry Mulyono; Benediktus Rolando; Alberta Ingriana (UNIVERSITAS PAKUAN, 2026)
Student satisfaction within technology-enhanced learning (TEL) environments is a pivotal factor influencing pedagogical effectiveness and higher education institutions' strategic positioning in a competitive landscape. However, critics highlight drawbacks, including dissatisfaction from the abrupt COVID-19 shift to online learning due to inadequate preparation, overburdened instructors, technostress, isolation in asynchronous courses, increased dropout rates, poor retention, and reputational damage. This systematic literature review synthesizes evidence from 64 peer-reviewed articles indexed in Scopus, published between 2020 and 2025 across multiple countries, to examine the key determinants of student satisfaction in TEL and their implications for institutional strategy and sustainability. The findings indicate that student satisfaction is a multifaceted construct shaped by pedagogical, technological, and support-related dimensions. These dimensions enhance learners’ perceptions and engagement, leading to improved retention, institutional reputation, enrollment outcomes, and overall competitiveness. The review also highlights the critical role of adaptive learning technologies and personalized instructional design in strengthening satisfaction. Furthermore, Institutions must strategically invest in robust TEL infrastructure and faculty development to optimize learning experiences and sustain long-term competitive advantage.